2016
DOI: 10.1261/rna.056499.116
|View full text |Cite
|
Sign up to set email alerts
|

Stable association of RNAi machinery is conserved between the cytoplasm and nucleus of human cells

Abstract: Argonaute 2 (AGO2), the catalytic engine of RNAi, is typically associated with inhibition of translation in the cytoplasm. AGO2 has also been implicated in nuclear processes including transcription and splicing. There has been little insight into AGO2's nuclear interactions or how they might differ relative to cytoplasm. Here we investigate the interactions of cytoplasmic and nuclear AGO2 using semi-quantitative mass spectrometry. Mass spectrometry often reveals long lists of candidate proteins, complicating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 65 publications
(91 reference statements)
4
57
0
Order By: Relevance
“…This assumption is in accordance with previous analysis suggesting that the nuclear RISC seems to be smaller than its cytoplasmic counterpart [37]. More recently, using a semi quantitative mass spectrometry approach, Kalantari et al [41] have confirmed the small size of the nuclear RISC, showing that the association of AGO2 with Gw182/TNRC6 (-A, -B, -C) and AGO3 is best preserved and more stable in both nuclei and cytoplasm whereas the AGO2 interaction with Dicer and TRBP is confined to the cytoplasm. Obviously, different conditions for biochemical purification may yield diverse compositions of the RISC.…”
Section: Mirisc and Mirnas: Cytoplasmic/nuclear Shuttlingsupporting
confidence: 90%
See 1 more Smart Citation
“…This assumption is in accordance with previous analysis suggesting that the nuclear RISC seems to be smaller than its cytoplasmic counterpart [37]. More recently, using a semi quantitative mass spectrometry approach, Kalantari et al [41] have confirmed the small size of the nuclear RISC, showing that the association of AGO2 with Gw182/TNRC6 (-A, -B, -C) and AGO3 is best preserved and more stable in both nuclei and cytoplasm whereas the AGO2 interaction with Dicer and TRBP is confined to the cytoplasm. Obviously, different conditions for biochemical purification may yield diverse compositions of the RISC.…”
Section: Mirisc and Mirnas: Cytoplasmic/nuclear Shuttlingsupporting
confidence: 90%
“…In fact, silencing of IPO8 reduces the pool of nuclear AGO2 [38]. AGO2 is lacking a nuclear localization signal unlike many components of the cytoplasmic RISC, including TNRC6 paralogs and Dicer [39,40,41,42,43], although a recent paper questions Dicer nuclear compartmentalization [44]. However, AGO2 overcomes this deficiency by combining with TNRC6A which possesses a nuclear localization signal (NLS) rather than a nuclear export signal (NES), and works as a nuclear–cytoplasmic shuttling protein to re-localize minimal miRISC to the nucleus [39,45].…”
Section: Mirisc and Mirnas: Cytoplasmic/nuclear Shuttlingmentioning
confidence: 99%
“…We also observed a small fraction of nuclear-localized PC-DHA-hsiRNAs. Active nuclear RISC complexes have been reported previously 4546 . The slow kinetics of delivery were analogous to the first generation of DHA-hsiRNA conjugates 47 .…”
Section: Resultsmentioning
confidence: 82%
“…Because of its established importance as an RNAi factor, we previously examined the potential for AGO2 to interact with proteins in cell nuclei. Mass spectrometry of the nuclear partners of AGO2, however, revealed only limited insights (Kalantari et al, 2016b). The GW182 paralogs TNRC6A, TNRC6B, and TNRC6C and the AGO variant AGO3 were the only partner proteins detected.…”
Section: Introductionmentioning
confidence: 99%